NEEDS ANALYSIS FOR ENGLISH FOR ACADEMIC PURPOSES: IMPORTANCE OF ACADEMIC LANGUAGE SKILLS FOR UNIVERSITY STUDENTS IN ETHIOPIA - Sileshi Chemir; Tamene Kitila (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to investigate undergraduate students’ needs analysis in English for Academic Purposes. In this study, three hundred-eight first-year students and forty-one EAP and subject area instructors at Wachemo University participated. The research employed a mixed-methods approach that utilized a questionnaire and a semi-structured interview to ascertain the important academic English language skills and sub-skills prioritized by participants. The findings revealed that the participants indicated all the academic language skills as important for students' academic study in the university. The instructors prioritized the academic language skills (academic reading and academic vocabulary) as important, whereas the students ranked the language skills (academic writing and academic speaking) as the first importance. The study emphasized the importance of conducting learners’ needs analysis before developing any English for Academic Purposes course. Findings in the current study could be provided as implications for course designers and recommendations for future studies. Keywords: Needs Analysis; English for Academic Purposes; Academic language skills; Ethiopia;